New Efficient Configurations for Sour Wastewater Treatment - Gadalla, Mamdouh A.; Ghallab, Ayat; Mansour, Ahmed M.; Ashour, Fatma H.; Elazab, Hany A. (Recent Innovations in Chemical Engineering, 2022)
Introduction: The environmental legislation on pollutant concentrations in aqueous effluents tends to tighten and increase due to the huge efforts devoted as a response to global warming and its related negative impact on our planet. As a result, sour water must be handled and processed properly to provide a high quality of stripped water with insignificant traces of NH3 and H2S. This approach must be achieved within the minimum operating costs. This scientific research investigates the stripping configurations of sour water effluents from various industries. The research also offers an insight into different scenarios and configurations to accomplish set targets satisfying the environmental law criteria. Methods: This research introduces a range of heat integration schemes for saving energy. Further, vapor recompression “VRC” technique is opted for its ability to maximize energy savings. This research also investigates the effect of operating and design variables on the stripped water quality, such as feed temperature, feed location, reflux split, and steam flow rate. The option of adding new equipment is also addressed to maximize heat integration and enhance the efficiency of the process. Thus, several schemes and process configurations are explored to treat the industrial sour water waste streams seeking better efficiency. Those configurations differ from one another in heat integration layout and VRC utilization. The energy efficiency and economics of the proposed configurations are considered decisive factors in this research study. The case study adopted in this research is based on published data taken from several iron and steel factories in South Korea named POSCO (Pohang Iron and Steel Corporation). Results: The obtained results of the treated wastewater streams guarantee that the effluent sour water obeys the standard environmental regulations, i.e., NH3 contents range from 30 to 80 ppm and H2S concentration falls below 0.1 ppm. The obtained results of the seven different scenarios are compared to the original case study. It is found that scenario 7 is the most economical solution saving 51.54 % of the total annual cost compared to the original case study while satisfying the treated water environmental regulations with a concentration of 3.19 ppm NH3 and 0.05 ppm H2S. Scenario 7 creates its own steam, unlike the original case study where steam utility is needed extensively. However, scenario 7 consumes 15 % more electricity than the original case study, but it also still shows 56.34 % less than the overall utility cost. Conclusion: The optimum process configuration can be employed for other sour water purification systems such as those used in petroleum refiners. An ongoing research work focuses on the use of internal heat integration for more energy savings and economic improvement.
Keywords: Sour water